Identifikasi dan analisis genetik bakteri karang pendegradasi senyawa herbisida 2,4-diklorofenoksi asetat di laut Jawa - SABDONO, Agus (Universitas Gadjah Mada, 2001)
The purposes of this study are to isolate, select, and identi@ the bacteria associated with corals, which are competent at degrading 2,4-Dichlorophenoxy acetate (2,4-D) compounds, and to analyze the gene, which are responsible for 2,4-D-degrading mechanism. The ecological and coral conditions and sampling sites selection are surveyed by scuba diving. The detection of 2,4-D herbicide residues in the tissues of dying corals is assayed, and the assay is continued on controlled toxicity experiments testing 2,4-D compounds on corals. The study of 2,4-D degradation on bacteria associated with corals is conducted by isolating the bacteria from coral tissues, purifying, performing degradation test, sensitivity test and kinetic study of growth and 2,4-D utilization. Molecular phylogenetic studies including DNA extraction, DNA amplification, RFLP, sequencing of 16s rRNA, and homology analyses by BLAST and RDP database program, are conducted. A phylogenetictree is constructed from the distance matrix by using CLUSTAL W. neighbourjoining method and PHYLYP program. Isolation of plasmid is done by PFGE. Curing plasmid is done by acridine orange treatment, and transformation is carried out by electrotransformation. The result showed that the coral condition on the Java Sea is very poor. Analysis of 2,4-D from coral tissues showed that the compound might cause coral mortality. In addition, the ecotoxicity study revealed that 2,4-D can kill coral on low concentration for brief exposure. Among 187 bacterial isolates, only 59 isolates are able to degrade 2,4-D compounds on EMBA indicator media. KP108, CP107, JG101, PP202 and PG303 isolates are selected based on the results of the sensitivity test and degradation test. Growth kinetics and 2,4-D substrate depletion experiment showed that the five isolates posses diverse kinetic parameters. Of the 5 isolates, PP202 has the highest capability of 2,4-D degradation. LineweaverBurk Linearization of the Michaelis-Menten equation is obtained Y = 0.0653 X + 1.3867 with maximum growth rate ( h h )of 0.72 h-', with saturated concentration (Cs) of 47.09 mg/l 2,4-D. The effect of 2,4-D concentration on the substrate removal rate (rs) is 0.0806 g/Vh and the specific substrate removal rate ( 0 ) is 0.027 h-' obtained from 200 mg/l 2,4-D concentration. RFLP analysis resulted i n 3 genotype difference OTU (Operational Taxonomy Unit): KP 108, JG10 1 and PP202 isolates having similar restriction pattern (genotype I), PG303 isolate (genotype 1 ) and CP107 isolate (genotype 111). Molecular determination of 16s 1 rRNA analyses and microbiological characteristic revealed that PP202 isolate is assigned to Vibrio natriegens (96 %), PG303 isolate is assigned to Vibrio